A Paradigm for the Twenty-first Century or Metaphorical Nonsense? The Enigma of Complexity Theory and Tourism Research - Speakman, Mark (Tourism planning & development, 2017)
For over 20 years, chaos and complexity theory has been advocated as a theoretical alternative to traditional methods of studying tourism. Nonetheless, despite its apparent potential, actual applications of the theory by tourism scholars remains low. This is related to the philosophical convictions of a traditionally Anglo-centric research community, the theoretical limitations of applying a concept originating from the natural sciences to a social science phenomena-in particular the use of metaphorical concepts to bridge the gap between the sciences-and the practical realities of applying complexity theory based strategies to real-world tourism concerns. The article recognises that the acceptance of chaos and complexity theory is ultimately subject to the individual's exclusive philosophy, thus leading to the emergence of three distinct groups within the tourism academic community-those who embrace the theory, those who steadfastly reject it, and those who await further theoretical and empirical research in order to refine their opinion.